Carbon-cryogel hierarchical composites as effective and scalable filters for removal of trace organic pollutants from water - Busquets, Rosa; Ivanov, Alexander E.; Mbundi, Lubinda; Hörberg, Sofia; Kozynchenko, Oleksandr P.; Cragg, Peter J.; Savina, Irina N.; Whitby, Raymond L D; Mikhalovsky, Sergey V.; Tennison, Stephen R.; Jungvid, Hans; Cundy, Andrew B. (Journal of Environmental Management, 2016)
Effective technologies are required to remove organic micropollutants from large fluid volumes to overcome present and future challenges in water and effluent treatment. A novel hierarchical composite filter material for rapid and effective removal of polar organic contaminants from water was developed. The composite is fabricated from phenolic resin-derived carbon microbeads with controllable porous structure and specific surface area embedded in a monolithic, flow permeable, poly(vinyl alcohol) cryogel.
Keywords: Composite materials; cryogel; Hierarchical structures; Phenolic carbon; Water treatment; Research Subject Categories::TECHNOLOGY::Engineering physics